Recent Progress on the Zweifel Olefination: An Update - Li, Xin; Song, Qiuling (Synthesis, 2023)
Over the past several decades, the Zweifel olefination has emerged as one of the most powerful and reliable tools for constructing C–C double bonds. This reaction features high efficiency, good versatility, avoids the use of transition metals, and typically affords perfect stereospecificity, making it superior to many other olefination methods. Since Aggarwal’s summary of the 50-year history of the Zweifel olefination in 2017, remarkable achievements have been made in terms of employing new organometallic species, performing reactions through electrochemical or photochemical pathways, and developing methods that furnish new types of products. This short review summarizes and discusses the very recent progress made on the Zweifel olefination and its latest applications in the synthesis of natural products.1 Introduction2 Zweifel Olefination with New Organometallic Species3 Zweifel Olefination with New Migrating Groups4 Electrochemical and Photocatalyzed Zweifel Olefinations5 New Elimination and Migration Patterns Involving the Zweifel Olefination6 Zweifel Olefination in Natural Product Synthesis7 Other Reactions Involving the Zweifel Olefination Mechanism8 Conclusions and Outlook
Keywords: Zweifel olefination; 1,2-migration; tetracoordinate; alkenyl boron; transition-metal-free; stereospecific